PENDIDIKAN KESEHATAN TEKHNIK MENYUSUI PADA IBU NIFAS HARI KE-3 DI DUSUN RAI CEHET: Pendidikan Kesehatan Tekhnik Menyusui pada ibu nifas hari ke-3 di dusun Rai Cehet - Padeng, Eufrasia Prinata; Seldista Manggul, Makrina; Yofrani Gloria Aroyo, Beatrix (LPPM Univ. Ibn Khaldun Bogor, 2022)
Breast milk is the best nutrition that is specifically given to newborns until they are 6 months old without other complementary foods. Breast milk is given to babies because it contains various components of antibodies, complete nutrition and is also easily digested by babies compared to formula milk. WHO 2016 The number of exclusive breastfeeding in the world is around 38 percent. Nationally in Indonesia, the coverage of infants receiving exclusive breastfeeding is 61.33% and has achieved the 2017 strategic plan, which is 44%. Obtained from the Ministry of Health in 2018 noted that the number of Early Breastfeeding Initiations in Indonesia increased from 51.8% in 2016 to 57.8 % in 2017. Although there has been an increase, this figure is still far from the 90% target. Mother's milk is the best intake for babies. It was obtained from Basic Health Research in 2018 that the lowest presentation was in East Nusa Tenggara Province, namely 25%. The goal after receiving counseling on breastfeeding techniques is that postpartum mothers are expected to be able to apply it to babies properly and correctly. The result of the health education is that breastfeeding mothers have been able to redemonstrate good and correct breastfeeding techniques. The conclusion is that there is an increase in knowledge and ability of breastfeeding techniques properly and correctly